Optimization of Frequency Stability in Hydraulic Load Frequency Control Systems Using Controllers with Filters - Laksono, Heru Dibyo; Rahmadani Putri , Dhea; Muharam , Mumuh; Wahyu Pratama , Rizki (Andalas Journal of Electrical and Electronic Engineering Technology, 2024)
This study meticulously investigates the design and analysis of a Load Frequency Control (LFC) system tailored explicitly for hydraulic power systems by employing diverse configurations of PID controllers, namely Proportional (P), Proportional-Integral (PI), Proportional-Derivative (PD), Proportional-Integral-Derivative (PID), Proportional-Derivative-Fractional (PDF), and Proportional-Integral-Derivative-Fractional (PIDF). The primary objective of this exploration is to improve frequency stability in response to various load fluctuations typical in hydraulic systems. A comprehensive evaluation of each controller's performance is conducted through extensive MATLAB simulations, focusing on critical performance metrics such as rise time, peak time, steady-state time, and maximum overshoot. The findings reveal that the PD and PDF controllers exhibit superior response characteristics, offering the fastest and most stable outcomes regardless of whether droop characteristics are utilized or filtering techniques are introduced. Although the implementation of filters significantly mitigates overshoot, it is evident that controllers incorporating droop characteristics tend to compromise optimal steady-state time stability. The overall analysis underscores the PD and PDF controllers as the preeminent solutions for ensuring frequency stability in hydraulic LFC systems, especially under abrupt and substantial load changes, thus positioning them as vital tools in enhancing hydraulic power system reliability and efficiency.